Perbankan KINERJA BANK SYARIAH YANG TERDAFTAR DI BURSA EFEK PADA MASA PANDEMI COVID-19: PENDEKATAN MAQASHID SYARIAH - Lamtana (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2022)
Abstract This study aims to analyze the performance of Islamic banks with the Maqashid Syariah approach. The analytical technique used is the Simple Additive Weighting Method (SAW) to solve multi-attribute decision problems. The sampling technique used is purposive sampling while the data comes from the annual reports of each bank. The results showed that among the 4 Islamic banks listed on the Indonesian stock exchange, only two banks entered the research criteria for research, namely Bank BTPN Syariah and Bank Panin Dubai Syariah. With the results of the study showing that when viewed from the sharia objectives of Tahdzib al-Fard, the first rank is BDSB with a score of 0.2486, then followed by BTPNS as the second rank with a score of 0.00335, judging from the goals of sharia Iqamah al-'Adl the first rank is held by BTPNS with a score of 0.3959 and the second place is PDSB with a score of 0.0761, then in the sharia goal of Jalb al-Maslahah the first place is won by PDSB with a score of 0.4326 and then the second place is BTPNS with a score of 0.1803. in the fourth sharia goal, namely Falah, the first winner is BTPNS with a score of 0.1243 where PDSB certainly ranks second with a total score of 0.0536. It was concluded that from the results of the research on the sharia objectives of the two BUS, namely PDSB and BTPNS, each of them twice ranked first in carrying out the objectives of Maqhasid Syariah. Keywords: Performance Assessment, Islamic Banking, Sharia Maqashid Index (IMS)